Brain metastasis from cervical carcinoma - Reyna-Villasmil, Eduardo (2018)
Cervical cancer is a frequent malignancy of women that spreads to lungs, supraclavicular lymph nodes, liver, and bones as distant metastasis. Prognosis is poor and survival varies from 3 to 6 months. We report the case of a 67-yearold woman with history of squamous cell carcinoma of cervix stage IIB 5 years ago treated with surgery plus radio-chemotherapy who presented walking impairment, headache and vomiting. Cranial magnetic resonance imaging revealed multiple lesions with increasing perilesional edema, T1-hypointense and T2-hyperintense. The patient died one week after the diagnosis. Necropsy findings showed poorly differentiated carcinoma of cervical origin.